The Influence of the COVID-19 Event on Entrepreneurial Intention of students in Shanghai - Yu, Yishu (2022)
ABSTRACT The outbreak of COVID-19 pandemic has had a considerable influence on people's life and work. Employment pressure has increased further and entrepreneurship, which can alleviate employment pressure, has suffered a lot. One of the most affected groups is student entrepreneurs. This study intends to understand the impact of COVID-19 pandemic on entrepreneurial intentions of Shanghai university students who are conducting their entrepreneurship at present, as well as the relationship between risk propensity and entrepreneurial intention and its moderating effect. Based on the event system theory, the impact of students' perceived strength of the pandemic on their entrepreneurial intentions and the mechanism of its effect were examined in terms of the attributes of pandemic event strength (novelty, criticality and, disruption). This study also investigated the association between risk propensity and the entrepreneurial intentions, as well as its function in moderating the effects of the pandemic event on entrepreneurial intentions. With the application of SPSS software, results from an online questionnaire survey study revealed that students’ perceptions of the novelty of the pandemic event were negatively related to their entrepreneurial intentions; students’ perceptions of the criticality of the pandemic event were insignificantly related to their entrepreneurial intentions; students’ perceptions of the disruption of the pandemic event were positively related to their entrepreneurial intentions. Moreover, students’ risk propensities were positively related to their entrepreneurial intentions, but its moderating effects were insignificant. The study highlighted the importance of external major public events to entrepreneurial intention and provided important theoretical value and practical insight into the correct understanding of the relationship between events and their related subjects.